Contrasts Between Poles and Ukrainians in Warsaw – Corpus Analysis of the Media Messages of Gazeta Wyborcza in 2015-2019 - Skibińska, Anna (Contrasts in humanities: literature, language, culture, 2023)
The article presents a corpus analysis of media messages about immigrants from Ukraine in Warsaw. The aim of the research was to compare headlines and texts and to identify keywords, words with the highest frequency and the most popular collocations. The korpusomat web application was used for the study. The results confirm that the image of Ukrainians is built on the basis of the opposition between locals and foreigners. The quantitative data for the headlines and for the texts were similar. The topics concerned mainly the work of immigrants. An important role in the media news was played by lemmas locating the places of events and the nationality of their participants.